STRATEGI KOMUNIKASI PEMASARAN TERPADU BALI UNITED DALAM MEMBANGUN BRAND IMAGE SEBAGAI KLUB SEPAKBOLA PROFESSIONAL - Yuliartha, Hady; Pascarani, Ni Nyoman Dewi; Alit Suryawati, I Gusti Agung (E-Jurnal Medium, 2017)
Bali united is one of the football club’s brand which in developing in Indonesia. It former name is Persisam Putra Samarinda and headquartered in Borneo. In February, 15th 2015 Putra Samarinda moved to Bali and changed it name to Bali United FC. Along with the name changing, Bali United build a new brand image as a pro-ffesional football club using the integrated marketing communication. The purpose of this study is to describe the integrated marketing communication strategy of Bali United to build their brand image. This research using qualitative descriptive approach that will explain the result from interview and some data that the researcher got from Bali United, which is then connected with the framework of thinking and the concept of integrated marketing communication. To be qualify as a professional football club, Bali United meet five aspects. Bali United using the medium of marketing communication as an integrated marketing communication strategy in building the brand image as professional footbal club. The medium are consist of advertising, sales promotion, direct marketing, intercative/internet marketing. Public relations, and personal selling. The message that was delivered by Bali United in every integrated marketing communication strategy always consistent to reach the brand image as a professional football club.   Keywords : brand image , integrated marketing communication , professional football club